Factors Related to Physical Activity Among the Elderly Population in Rural Thailand - Plernta Ethisan; Ratana Somrongthong; Jamil Ahmed; Ramesh Kumar; Robert S. Chapman (SAGE Publishing, 2017)
Physical activity in later years of life is not only essential to healthy aging and independent functioning, but it also helps prevent chronic diseases. We aimed this cross-sectional study to assess the prevalence of physical activity and associated factors among rural elderly Thais. We conducted this study on a sample of 300 elderly in 2 rural districts of Phranakornsiayutthaya province in Thailand. The mean age of participants were 67.5±6 years and 42% of them did not perform physical activity. Prevalence of vigorous and moderate intensity physical activity was 43.7% and 48.7%, respectively. About 43.7% elderly used any active transport and spent 2.81 hours on sedentary activities, daily. Females and those with enough income were 3.64 and 0.59 times, respectively, less likely to be physically active ( P < .05). Our study concluded that almost half of the rural Thai elderly were physically inactive. Also male and wealthy elderly were less likely to be engaged in physical activity. We recommend for improved efforts to involve rural Thai elderly in physical activity by offering them opportunities for locally relevant recreational and leisure time physical activities, with special focus on males and higher income elderly.